Indeks Ekonomi Digital (IED): Pembentukan, Analisis, dan Implikasinya bagi Kebijakan Ekonomi Digital Level Provinsi - Feriyanto, Muhamad; Lesmana, Muhammad Erza (Seminar Nasional Official Statistics, 2025)
The rapidly growing global digital economy offers significant transformative potential for Indonesia. However, regional digital divides and the lack of comprehensive measurement tools are crucial issues that hinder the optimization of potential and the formulation of data-driven policies. This study aims to develop a Provincial Digital Economy Index (DEI) to measure the development of the digital economy in Indonesia. Three methods were used in the formation of the DEI: weighted average with PCA and entropy weights, and geometric mean. The results show that the PCA-weighted I is relatively more robust against extreme values. The PCA-weighted DEI has a strong positive correlation (